THE INFLUENCE OF JOB RELATED ANXIETY AND GREEN HUMAN RESOURCE MANAGEMENT PRACTICE ON JOB PERFORMANCE WITH EMPLOYEE BEHAVIOR AS A MEDIATING VARIABLE AT PT SAMATOR GAS INDUSTRI TEBING TINGGI - Eryani; Indra Welly Arifin; Kumala Vera Dewi (RADJA PUBLIKA, 2024)
The type of research used is quantitative research, a research method that places greater emphasis on the aspect of objective measurement of social phenomena. The data source used in this research is a primary data source which was directly collected by the researcher from the first source. The data analysis method used by researchers is the Structural Equation Model (SEM) based on Partial Least Square (PLS). Based on the research results, the first hypothesis is that Job Related Anxiety (X1) has a significant influence on the Employee Behavior (Z) variable. The second hypothesis is that Green Human Resource Management Practice (X2) has a significant influence on the Employee Behavior variable (Z). The third hypothesis is that Job Related Anxiety (X1) has a significant influence on the Job Performance variable (Y). The fourth hypothesis is that Green Human Resource Management Practice (X2) has a significant influence on the Job Performance variable (Y). The fifth hypothesis is that Employee Behavior (Z) has a significant influence on the Job Performance (Y) variable. The sixth hypothesis concludes that Employee Behavior (Z) has a positive and significant effect in mediating Job Related Anxiety (X1) on Job Performance (Y). The seventh hypothesis concludes that Employee Behavior (Z) has a positive and significant effect in mediating Green Human Resource Management Practice (X2) on Job Performance (Y).